2023
DOI: 10.1101/2023.06.12.544549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural thermal stress-hardening of corals through cold temperature pulses in the Thai Andaman Sea

Abstract: Thermal variability can render corals stress resistant through a phenomenon coined as stress-hardening induced by environmental priming. Fluctuations that involve high temperature peaks have been commonly investigated, however, the effects of a stress-hardening stimulus generated by cold-water pulses has rarely been studied. Offshore island reefs in the Andaman Sea offer an ideal natural setting to study these effects, as cooling water of internal waves induce strong variability with peak intensity in January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Our aquarium experiments demonstrated that thermal preconditioning can be applied to stressharden corals and enhance their ability to cope with an acute heat stress pulse, contributing to the growing body of literature that has primarily reported this phenomenon from the field, including only few ex-situ studies (Ainsworth et al, 2016;Bay & Palumbi, 2015;Brown et al, 2023;Hackerott et al, 2021;Majerova et al, 2021;Martell, 2023;Wall et al, 2023). At the same time, our systematic and multi-species comparison has revealed that the receptiveness to the stress-hardening effects of thermal preconditioning strongly varied between the coral species.…”
Section: Thermal Preconditioning Enhances Coral Heat-stress Tolerancementioning
confidence: 57%
See 1 more Smart Citation
“…Our aquarium experiments demonstrated that thermal preconditioning can be applied to stressharden corals and enhance their ability to cope with an acute heat stress pulse, contributing to the growing body of literature that has primarily reported this phenomenon from the field, including only few ex-situ studies (Ainsworth et al, 2016;Bay & Palumbi, 2015;Brown et al, 2023;Hackerott et al, 2021;Majerova et al, 2021;Martell, 2023;Wall et al, 2023). At the same time, our systematic and multi-species comparison has revealed that the receptiveness to the stress-hardening effects of thermal preconditioning strongly varied between the coral species.…”
Section: Thermal Preconditioning Enhances Coral Heat-stress Tolerancementioning
confidence: 57%
“…Acclimatization relies on the adjustments of plastic phenotypic traits that can be induced by the changes in gene expression. These allow organisms to reduce stress responses by being better able to cope with extreme environmental conditions without permanent DNA modifications (DeMerlis et al, 2022;Majerova et al, 2021;Roik et al, 2023;Wall et al, 2023;Ziegler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that the thermal history of the parental colonies in the field, as well as the early exposure to elevated temperatures of the offspring, have contributed to the acclimation success of corals in our experiment. Since exposure to thermal variability is a good predictor of high stress-resistance and large plasticity in corals (Hackerott et al, 2021;Rivest et al, 2017;M. Wall et al, 2023), the thermal history of the parents from the Luminao reef flat, which has a large thermal range, could be one explanation, why the offspring was able to acclimate to the new elevated temperature of 31 °C.…”
Section: Underlying Mechanisms Of Observed Coral Responses Under Elev...mentioning
confidence: 99%
“…The increasing severity and frequency of deteriorating coral bleaching events (Donner et al, 2005;van Hooidonk et al, 2013) have been driving the development of proactive measures that aim to protect corals from thermal stress (van Oppen et al, 2015). Some of the anticipated approaches consider selection of thermally tolerant coral specimens for reef restoration (Humanes et al, 2021;Morikawa & Palumbi, 2019), while others intend to use thermal preconditioning treatments aiming to improve thermal tolerance of nursery corals (DeMerlis et al, 2022;Hancock et al, 2021;Henley et al, 2022;M. Wall et al, 2023).…”
Section: Ecological Implications and Considerations For Active Reef R...mentioning
confidence: 99%
See 1 more Smart Citation